Techniques of Vibration And End-Point Trajectory Control of Flexible Manipulator - Mohd Ashraf, Ahmad; Zaharuddin, Mohamed (2009)

(untitled)
This paper presents investigations into the development of control schemes for end-point vibration suppression and input trajectory of a flexible manipulator. A constrained planar single- link flexible manipulator is considered and the dynamic model of the system is derived using the assumed mode method. To study the effectiveness of the controllers, initially a Linear Quadratic Regulator (LQR) is developed for control of rigid body motion. This is then extended to incorporate a non-collocated PID controller and a feedforward controller based on input shaping techniques for control of vibration (flexible motion) of the system. For feedforward controller, the positive input shapers are proposed and designed based on the properties of the system. Simulation results of the response of the manipulator with the controllers are presented in time and frequency domains. The performances of the control schemes are assessed in terms of level of vibration reduction, input tracking capability and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.